Vulnerability of northern rocky mountain forests under future drought, fire, and harvest - Stenzel, Jeffrey E.; Kolden, Crystal A.; Buotte, Polly C.; Bartowitz, Kristina J.; Walsh, Eric W.; Hudiburg, Tara W. (Frontiers in Forests and Global Change, 2023)
Novel climate and disturbance regimes in the 21st century threaten to increase the vulnerability of some western U.S. forests to loss of biomass and function. However, the timing and magnitude of forest vulnerabilities are uncertain and will be highly variable across the complex biophysical landscape of the region. Assessing future forest trajectories and potential management impacts under novel conditions requires place-specific and mechanistic model projections. Stakeholders in the high-carbon density forests of the northern U.S. Rocky Mountains (NRM) currently seek to understand and mitigate climate risks to these diverse conifer forests, which experienced profound 20th century disturbance from the 1910 “Big Burn” and timber harvest. Present forest management plan revisions consider approaches including increases in timber harvest that are intended to shift species compositions and increase forest stress tolerance. We utilize CLM-FATES, a dynamic vegetation model (DVM) coupled to an Earth Systems Model (ESM), to model shifting NRM forest carbon stocks and cover, production, and disturbance through 2100 under unprecedented climate and management. Across all 21st century scenarios, domain forest C-stocks and canopy cover face decline after 2090 due to the interaction of intermittent drought and fire mortality with declining Net Primary Production (NPP) and post-disturbance recovery. However, mid-century increases in forest vulnerability to fire and drought impacts are not consistently projected across climate models due to increases in precipitation that buffer warming impacts. Under all climate scenarios, increased harvest regimes diminish forest carbon stocks and increase period mortality over business-as-usual, despite some late-century reductions to forest stress. Results indicate that existing forest carbon stocks and functions are moderately persistent and that increased near-term removals may be mistimed for effectively increasing resilience.